Using modelling and simulation based study methods in coal industry technological improvement - Andras, Iosif; Ilias, Nicolae; Cioara, Inga; Mihaileanu, A. C.; Nicolae, F. (NTU "KhPI", 2009)
The trend to wards the increase of the role of coalin the electricity production reveals its importance among the primary energy resources balance. So, from the point of view of the structure of the primary energy, the evolution fore cast performed by IEA highlights that in the future, aquarter of the world wide used energy primary resources will be based on coal. The share of coalin energy production willgrow, as the total energy demand growth with 60% in the next 20 years.
Использование моделирования и имитационных методов изучения в промышленности